1954
DOI: 10.1021/ba-1954-0011.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Gelation with Pectin

Abstract: Gelation studies have sought to establish the background for a theory of pectin gel formation. Factors investigated that control the properties of pectin gels were: pH, degree of esterification, effect of acylation, temperature, and molecular weight. Elastic moduli of pectin gels decrease as the degree of esterification or of acylation decreases; they remain practically constant from 0° to 50° C. and decrease rapidly with further increase in temperature; and they are controlled by number average molecular weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1959
1959
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…According to Owens et al, while heating PEC solutions, in the temperature range between 0 °C to 50 °C, there is no detection of thickening of the solution. Contrarily, during cooling, hydrogen bonding is enhanced, providing strong gels [ 41 ]. The behavior of PEC is in accordance with our everyday experience.…”
Section: Resultsmentioning
confidence: 99%
“…According to Owens et al, while heating PEC solutions, in the temperature range between 0 °C to 50 °C, there is no detection of thickening of the solution. Contrarily, during cooling, hydrogen bonding is enhanced, providing strong gels [ 41 ]. The behavior of PEC is in accordance with our everyday experience.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular chain length, spacial configurations and complexity of side chain structure influence the solubility and gelling properties of pectins (Bonner, 1950;Deuel and Solms, 1954). It has been found that fuIIy esterified apple pectin can form gels in a 60% solids medium (approximately as in cell walls) which are firmer than those formed with the original pectin; also that increased esterification in certain ranges appears to be associated with decreased solubility of the pectin (Owens et al 1954). It is noteworthy here that the highest degree of esterification was found in both clingstone and freestone peaches at early ripening to hard ripe stages before and after which degree of pectin esterification was appreciably lower.…”
mentioning
confidence: 99%
“…Therefore, it was structurally weaker than the mixture with pea protein and apple pectin, which is most likely due to the lower molecular weight of the sugar beet pectin (45.0 kDa) compared with the apple pectin (64.6 kDa). 28 All the different control samples exhibited viscoelastic properties (tan ⊐ = 0.67-0.94) that facilitated a good balance of adhesion and cohesion. Therefore, all control samples were sticky, showing a cohesive failure (Table 1), and thus were generally suitable as food glues.…”
Section: Resultsmentioning
confidence: 95%